2012
DOI: 10.3109/14767058.2011.648241
|View full text |Cite
|
Sign up to set email alerts
|

Communication in the neonatal intensive care unit: a continuous challenge

Abstract: In NICU, communication between the members of the team and the newborn's parents may be improved by specific tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…A variety of models for communication training of both NICU physicians 73 , 82 , 83 , 84 , 85 , 86 , 87 , 88 and nurses 89 exist. Each NICU should tailor their efforts to the size, composition and needs of their staff, balanced with the resources available to the hospital.…”
Section: Models Of Communication Trainingmentioning
confidence: 99%
“…A variety of models for communication training of both NICU physicians 73 , 82 , 83 , 84 , 85 , 86 , 87 , 88 and nurses 89 exist. Each NICU should tailor their efforts to the size, composition and needs of their staff, balanced with the resources available to the hospital.…”
Section: Models Of Communication Trainingmentioning
confidence: 99%
“…Recognizing that parents are important contributors to quality care of their children, hospitals are increasingly emphasizing FCC 8 and evaluating whether FCC fosters parent engagement and satisfaction with care. 9,10 Several studies have shown that interventions designed to improve communication and maximize the FCC approach can be delivered successfully, 11,12 but some have indicated that implementation of FCC policies may require additional education, training, and resources to truly be effective. 12 Two NICU-focused studies found that the discrepancy between parents' expectations of what care should be and its actual reality was associated with a lack of satisfaction with care, and confirmed that perceptions of care play a large role in parent satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Several studies have shown that interventions designed to improve communication and maximize the FCC approach can be delivered successfully, 11,12 but some have indicated that implementation of FCC policies may require additional education, training, and resources to truly be effective. 12 Two NICU-focused studies found that the discrepancy between parents' expectations of what care should be and its actual reality was associated with a lack of satisfaction with care, and confirmed that perceptions of care play a large role in parent satisfaction. 13,14 Similarly, a relationship between maternal social support (both in and out of the hospital) and satisfaction with infant care has consistently been observed.…”
Section: Introductionmentioning
confidence: 99%
“…European and international literature dealing with severely preterm birth (gestational age, <28 weeks or low birth weight <1,500 g; Taylor et al 2000;Bhutta et al 2002;McGrath & Sullivan 2002;O'Keeffe et al 2003;Marlow 2004;Mulder et al 2009;Biasini et al 2012) and moderately preterm birth (gestational age, <34/5 weeks and weight <2,500/>1,500 g; Chyi et al 2008;Huddy et al 2001;Van Baar et al 2009;Heinonen et al 2010) have defined a specific background of the likely configurations of disadaptive functioning with regards to cognitive, emotional, and behavioral fields, which characterize the developmental paths of preterm children. The probability that such configurations could be detected at preschool age as precursors of real learning disabilities and school failure has already been claimed by the authors of this article in a previous research project Perricone et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%